Worth your weight: Experimental evidence on the benefits of obesity in low-income countries - Elisa Macchi (University of Zurich, Department of Economics, 2022)
I study the economic value of obesity - a seemingly inconsequential but unhealthy status symbol in poor countries. Randomizing decision-makers in Kampala, Uganda to view weight-manipulated portraits, I make four findings. First, obesity is perceived as a reliable signal of wealth rather than beauty and health. Second, being obese facilitates access to credit: in a real-stakes experiment involving loan officers, the obesity premium is comparable to raising borrower self-reported earnings by 60%. Third, asymmetric information drives this premium, which drops significantly when more financial information is provided. Fourth, obesity benefits and wealth-signaling value are commonly overestimated, raising the cost of healthy behaviors.
Keywords: I10; O10; Z13; 330; Obesity; status; asymmetric information